Arterial CNS Involvement in Behcet's Disease - Akman\\-Demir, Gulsen; Birday\\-Shugaiv, Erkingul; Kurtuncu, Murat; Mutlu, Melike; Barlas\\-Yesilot, Nilufer; Tuzun, Erdem; Coban, Oguzhan; Bahar, Sara (LIPPINCOTT WILLIAMS \& WILKINS, 2013)
65th Annual Meeting of the American-Academy-of-Neurology (AAN), San Diego, CA, MAR 16-23, 2013